Central Valley, California and Other Forms of the Third Landscape: Reading (From) Infrastructure - Valls Boix, Juan Evaristo (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
The aim of this paper is to explore a form of comparative reading in a materialist key that we call the reading of (and from) infrastructure. This form of reading is relevant because it allows us to assess the political scope of literature, which will be understood here from a hybrid reflection between biopolitics (Agamben) and aesthetics (Rancière). Of all the infrastructures, this article will address that of access to land, that is, our relationship with space, the habitability of cities. The precariousness of this infrastructure will be studied through a resignification of Gilles Clément's concept of "third landscape", a spatial concept that will be shown to be operative to analyze various samples of American short narrative in recent years. This analysis will allow us to delimit a tendency in contemporary short story usually labeled as "realism", which will be referred to here as the "School of Banality", a term in opposition with the American tradition of the postmodern novel and its successors.
Keywords: Third Landscape; Heterotopy; precariousness; American short fiction; Anthony Veasna So